Continuous Intraarterial Nimodipine Infusion for the Treatment of Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage: A Retrospective, Single-Center Cohort Trial - Kramer, Andreas; Selbach, Moritz; Kerz, Thomas; Neulen, Axel; Brockmann, Marc A.; Ringel, Florian; Brockmann, Carolin (Frontiers in Neurology, 2022)
Background Delayed cerebral ischemia (DCI) occurs after aneurysmal subarachnoid hemorrhage (aSAH). Continuous intraarterial nimodipine infusion (CIAN) is a promising approach in patients with intracranial large vessel vasospasm (LVV). The objective of this retrospective single-center cohort study was to evaluate the outcome in aSAH-patients treated with CIAN. Methods CIAN was initiated and ended based on the clinical evaluation and transcranial Doppler (TCD), CT-angiography, CT-perfusion (PCT), and digital subtraction angiography (DSA). Nimodipine (0.5–2.0 mg/h) was administered continuously through microcatheters placed in the extracranial internal carotid and/or vertebral artery. Primary outcome measures were Glasgow Outcome Scale (GOS) at discharge and within 1 year after aSAH, and the occurrence of minor and major (<⅓ and >⅓ of LVV-affected territory) DCI-related infarctions in subsequent CT/MRI-scans. Secondary outcome measures were CIAN-associated complications. Results A total of 17 patients underwent CIAN. Median onset of CIAN was 9 (3–13) days after aSAH, median duration was 5 (1–13) days. A favorable outcome (GOS 4–5) was achieved in 9 patients (53%) at discharge and in 13 patients within 1 year (76%). One patient died of posthemorrhagic cerebral edema. Minor cerebral infarctions occurred in five and major infarctions in three patients. One patient developed cerebral edema possibly due to CIAN. Normalization of PCT-parameters within 2 days was observed in 9/17 patients. Six patients showed clinical response and thus did not require PCT imaging. Conclusion The favorable outcome in 76% of patients after 1 year is in line with previous studies. CIAN thus may be used to treat patients with severe therapy-refractory DCI.